Lifetime and current depression in the German National Cohort (NAKO): original investigation - Streit, Fabian; Zillich, Lea; Frank, Josef; Kleineidam, Luca; Wagner, Michael; Baune, Bernhard T.; Klinger-König, Johanna; Grabe, Hans Jörgen; Pabst, Alexander; Riedel-Heller, Steffi Gerlinde; Schmiedek, Florian; Schmidt, Börge; et al. (The world journal of biological psychiatry, 2023)
The present study introduces the assessment of depression and depressive symptoms in the German National Cohort (NAKO), a population-based mega cohort. Distribution of core measures, and associations with sociodemographic factors are examined. The current analysis includes data from the first 101,667 participants (NAKO data freeze 100,000). Depression and depressive symptoms were assessed using a modified version of the depression section of the Mini-International Neuropsychiatric Interview (MINI), self-reported physician’s diagnosis of depression, and the depression scale of the Patient Health Questionnaire (PHQ-9). A lifetime physician’s diagnosis of depression was reported by 15.0% of participants. Of those, 47.6% reported having received treatment for depression within the last 12 months. Of the subset of 26,342 participants undergoing the full depression section of the modified MINI, 15.9% were classified by the MINI with a lifetime depressive episode. Based on the PHQ-9, 5.8% of the participants were classified as currently having a major or other depression by the diagnostic algorithm, and 7.8% according to the dimensional assessment (score ≥ 10). Increased frequency of depression measures and higher depression scores were observed in women and participants with lower education level or a family history of depression. The observed distributions of all depression measures and their associations with sociodemographic variables are consistent with the literature on depression. The NAKO represents a valuable epidemiologic resource to investigate depression, and the range of measures for lifetime and current depression allows users to select the most suitable instrument for their specific research question.